Refuse - Randall, Julian (University of Pittsburgh Press, 2018)
Set against the backdrop of the Obama presidency, Julian Randall's Refuse documents a young biracial man's journey through the mythos of Blackness, Latinidad, family, sexuality and a hostile American landscape. Mapping the relationship between father and son caught in a lineage of grief and inherited Black trauma, Randall conjures reflections from mythical figures such as Icarus, Narcissus and the absent Frank Ocean. Not merely a story of the wound but the salve, Refuse is a poetry debut that accepts that every song must end before walking confidently into the next music.
Keywords: American poetry -- 21st century.; FICTION -- General.; American poetry; 2000-2099; poetry.; Poetry; Poetry.; Poésie.